Asymmetric vortex dynamics in two-dimensional Bose–Einstein condensate with harmonic trap potential - Chenghao Li; Zhengliang Liu; Yuan Ren; Ying Wang; Hao Wu; Zhenyu Xiong; Xiangyu Ran (AIP Advances, 2022)
Based on the two-dimensional Gross–Pitaevskii equation model, we investigated the asymmetric vortex evolution of two-dimensional Bose–Einstein condensates in a harmonic potential trap with polar direction perturbation. This corresponds to the generation of an asymmetric vortex evolution mode under initial vortex light manipulation together with polar direction perturbation. Unlike most of the prior work on this topic that uses a pure numerical method for the system under study, we use an exact analytical method rather than numerical simulation to investigate the key features of the system evolution dynamics in this study. Based on the variational method, and for different system parameter settings including the strength of the harmonic oscillator potential and the nonlinear interaction, we derived two evolution modes, namely, the periodic evolution oscillation mode and the monotonic decay mode, and pictorially demonstrated the evolution patterns of the system. In addition, we investigated the scenario when the system is in the rotating state, which corresponds to the action of the quadratic centrifugal potential. Notably, we also identified the damping effects for the two modes with increasing angular velocity, whose upper limit value corresponds to the constant vortex pattern of the system. Our theoretical results can be used to guide the experimental investigation of asymmetric vortex evolution in two-dimensional Bose–Einstein condensates.